The Essence of Authenticity - Dammann, Olaf; Friederichs, Katja M.; Lebedinski, Sabine; Liesenfeld, Kerstin M. (Frontiers in Psychology, 2021)
Abstract In this paper we build upon the model of authenticity proposed by David Lehman and coworkers (2019), which includes the dimensions consistency, conformity, and connection. We expand this “3C-view” by adding a fourth dimension, continuity, which results in what we have come to call “4C-view of authenticity”. We discuss our proposal from a process perspective and emphasize that congruence might be a reasonable candidate for a concept that unifies the four dimensions of authenticity.